2019
DOI: 10.1002/cne.24628
|View full text |Cite
|
Sign up to set email alerts
|

Selective Cre‐mediated gene deletion identifies connexin 43 as the main connexin channel supporting olfactory ensheathing cell networks

Abstract: Many functions of glial cells depend on the formation of selective glial networks mediated by gap junctions formed by members of the connexin family. Olfactory ensheathing cells (OECs) are specialized glia associated with olfactory sensory neuron axons. Like other glia, they form selective networks, however, the connexins that support OEC connectivity in vivo have not been identified. We used an in vivo mouse model to selectively delete candidate connexin genes with temporal control from OECs and address the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 57 publications
2
11
0
Order By: Relevance
“…Indeed, OECs and astrocytes are electrically and dye‐coupled and C×43kiECFP reporter mice showed that juxtaglomerular astrocytes as well as OECs can express C×43. This observation was further substantiated by our and other immunostainings (Piantanida et al, ; Rela et al, ; Roux et al, ; Theofilas, Steinhauser, Theis, & Derouiche, ). Hence, astrocytes and OECs might form homotypic gap junctions by C×43, in contrast to panglial coupling between astrocytes and oligodendrocytes, in which heterotypic gap junctions are built between C×43 (astrocyte) and C×47 (oligodendrocyte) or between C×30 (astrocyte) and C×32 (oligodendrocyte) (Orthmann‐Murphy, Freidin, Fischer, Scherer, & Abrams, ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Indeed, OECs and astrocytes are electrically and dye‐coupled and C×43kiECFP reporter mice showed that juxtaglomerular astrocytes as well as OECs can express C×43. This observation was further substantiated by our and other immunostainings (Piantanida et al, ; Rela et al, ; Roux et al, ; Theofilas, Steinhauser, Theis, & Derouiche, ). Hence, astrocytes and OECs might form homotypic gap junctions by C×43, in contrast to panglial coupling between astrocytes and oligodendrocytes, in which heterotypic gap junctions are built between C×43 (astrocyte) and C×47 (oligodendrocyte) or between C×30 (astrocyte) and C×32 (oligodendrocyte) (Orthmann‐Murphy, Freidin, Fischer, Scherer, & Abrams, ).…”
Section: Discussionsupporting
confidence: 86%
“…Indeed, OECs and astrocytes are electrically and dye-coupled and C×43kiECFP reporter mice showed that juxtaglomerular astrocytes as well as OECs can express C×43. This observation was further substantiated by our and other immunostainings (Piantanida et al, 2019;FIGURE 7 Gap junctions mediate transmission of Ca 2+ signals between OECs and astrocytes. (a) Induction of Ca 2+ transients in astrocytes (black trace) via the photolysis of caged tACPD resulted in delayed Ca 2+ responses in OECs (grey trace) that were suppressed by CBX (150 μM).…”
Section: Panglial Ca 2+ Signaling Of Astrocytes and Oecs Depends Onsupporting
confidence: 77%
“…OECs within the OB and OM have distinct gene expression profiles (Guerout et al, ), but it is currently unclear whether these genetically and spatially separate populations mediate common physiological mechanisms that ensure normal homeostasis and continual neuronal turnover. Previous studies in acute slices of the OB from juvenile mice have described a variable contribution of certain types of membrane channels to shaping the electrical responses of OECs (Piantanida et al, ; Rela et al, , ). Following the loss of gap junctional coupling, these OECs display heterogeneous membrane currents, with variable contributions from hyperpolarization‐activated inward rectifier K + currents and depolarization‐activated outward rectifier K + currents.…”
Section: Introductionmentioning
confidence: 99%
“…The physiological functions of peripheral OECs remain poorly understood at a cellular and molecular level (Chen, Kachramanoglou, Li, Andrews, & Choi, 2014;Gomez et al, 2018), and so it is currently unclear why this subtype of OECs could more successfully encourage neuronal regeneration. Much of our current understanding of neuroglial interactions comes from structural, molecular, and functional studies of rodent OECs, from either the OM or OB (Guerout et al, 2010;Hayat, Wigley, & Robbins, 2003;Higashi et al, 2001;Piantanida et al, 2019;Rash et al, 2005;Rela, Bordey, & Greer, 2010;Rela, Piantanida, Bordey, & Greer, 2015;Rieger, Deitmer, & Lohr, 2007). Studies of excised human OM tissues have also helped identify common markers in vivo (Choi, Law, Raisman, & Li, 2008;Liu et al, 2010;Oprych, Cotfas, & Choi, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation